Ephedra as a gymnosperm evo‐devo model lineage. Issue 3 (27th January 2021) - Di Stilio, Verónica S.; Ickert‐Bond, Stefanie M.
Abstract: Established model systems in the flowering plants have greatly advanced our understanding of plant developmental biology, facilitating in turn its investigation across diverse land plants. The reliance on a limited number of model organisms, however, constitutes a barrier for future progress in evolutionary developmental biology (evo‐devo). In particular, a more thorough understanding of seed plant character evolution and of its genetic and developmental basis has been hampered in part by a lack of gymnosperm model systems, since most are trees with decades‐long generation times. Guided by the premise that future model organisms should be selected based on their character diversity, rather than simply phylogenetic "position, " we highlight biological questions of potential interest that can be addressed via comparative studies in Ephedra (Gnetales). In addition to having relatively small genomes and shorter generation times in comparison to most other gymnosperms, Ephedra are amenable to investigations on the evolution of the key reproductive seed plant innovations of pollination and seed dispersal, as well as on polyploidy, and adaptation to extreme environments. Abstract : Ephedra (Gnetales), a potential gymnosperm model lineage: Seed cone morphology, seed dispersal strategies, and genome size in relation to other gymnosperms. Research Highlights: This perspective highlights Ephedra (Gnetales) as the next gymnosperm evo‐devo model system to facilitate investigation of the evolution of key developmental innovations in seed plant reproduction.